2004
DOI: 10.1590/s1516-635x2004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Different sodium levels and electrolyte balances in pre-starter diets for broilers

Abstract: An experiment with 400 one-day-old male chicks (Ross) was conducted to evaluate the effects of different Na levels (0.10, 0.22, 0.34 and 0.46%) and different cation/anion balances (Na+K-Cl) (100, 150, 200, 250 and 300 meq/kg) in pre-starter diets on broiler performance. The corn and soybean-based diets had 22% crude protein and 2,900 kcal/kg metabolizable energy and were fed ad libitum. Performance data showed a positive quadratic effect of increasing Na levels on feed and water consumption, weight gain and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Maiorka et al (2004) observed a quadratic response for increasing Na levels (from 0.10 to 0.46%) in pre-starter diets on body weight gain (BWG), feed conversion ratio (FCR), FI and water consumption. It has been demonstrated that Na has an important role in feed intake (FI) just after hatching for stimulating the secretion and activity of certain digestive enzymes.…”
Section: Dietary Electrolytes and Growth Performancementioning
confidence: 99%
“…Maiorka et al (2004) observed a quadratic response for increasing Na levels (from 0.10 to 0.46%) in pre-starter diets on body weight gain (BWG), feed conversion ratio (FCR), FI and water consumption. It has been demonstrated that Na has an important role in feed intake (FI) just after hatching for stimulating the secretion and activity of certain digestive enzymes.…”
Section: Dietary Electrolytes and Growth Performancementioning
confidence: 99%
“…Vieira, Penz, Pophal, and Almeida () reported that broilers aged 1–7 days in a 0.48% Na + group had the highest mortality rate. Maiorka, Magro, and Bartels () showed that the optimum ADG and ADFI resulted when the Na + level was 0.4%, higher than the NRC recommendation. Koreleski, Światkiewicz, and Arczewska () found that there was a positive correlation between dietary Na + and growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…This also happened in experiment 2, with total sodium levels of 0.178-0.384%. In studies with pre-starter broilers, Maiorka et al (2004) reported that 0.45% dietary sodium resulted in the highest water intake compared with 0.10, 0.22, and 0.34%. When sodium bicarbonate was diluted in water (experiment 2), the basal diet contributed with 0.109% sodium, and sodium levels …”
Section: Influence Of Environmental Temperature and Electrolyte Balanmentioning
confidence: 99%